PPPUD Group "Maja Tani Soka" in Banjar Soka, Senganan Village Penebel District, Tabanan District - Made Sri Yuliartini; Luh Kartini; Anak Agung Ngurah Mayun Wirajaya; Ida bagus Komang mahardika (Asian Journal of Community Services, 2023)
Regional Featured Product Development Program Activities in Banjar Soka, Senganan Village, Penebel, Tabanan, Bali at the Maja Tani Soka Group, engaged in organic farming, namely producing organic red rice.  The availability of rice is not sustainable, partners want to increase production both in quantity and quality, Partners do not yet understand the proper and correct technology for cultivating plants using an organic system; Organic fertilizer has not been fermented properly.  Solutions by providing appropriate technology in cultivating rice plants and making organic fertilizer, organic pesticides and packaging. The method is technology transfer and introducing science and technology, namely outreach activities, training, mentoring, demonstration plots; both partners are actively and creatively invited to work together. The result is superior products of Maja liquid organic fertilizer and Maja organic pesticides and also an increase in the production of organic red rice qualitatively and quantitatively and the welfare of partners increases